Anatomical Depiction: How Showing a Product's Inner Structure Shapes Product Valuations - Kang, Seo Yoon; Kim, Junghan; Lakshmanan, Arun (Journal of Marketing, 2025)
Anatomical depiction is a technique whereby the product is decomposed into components that are spatially arranged layer by layer to visually explicate its inner structure. The authors demonstrate that anatomical depiction, compared with nonanatomical depiction, enhances product valuation. This effect occurs because anatomical depiction elicits a “coming together” of the inner components in consumers’ minds, thereby evoking a gestalt image of the product—a process labeled “simulated assemblage.” The elicitation of simulated assemblage in turn boosts confidence in the product's performance. Two field experiments demonstrate that anatomical depiction leads to greater engagement in online settings such as peer-to-peer selling and social media advertising. Subsequently, seven laboratory and online experiments show when and how anatomical depiction elicits simulated assemblage (Studies 1a–c), test the process underlying the effect of anatomical depiction on product valuation (Studies 2a–b), and delineate two boundary conditions, showing that the positive effect of anatomical (vs. nonanatomical) depiction attenuates for consumers higher (vs. lower) in technology anxiety (Study 3) and when consumers have a hedonic (vs. utilitarian) consumption goal (Study 4). Collectively, this work provides insights to firms on how and when to use anatomical depiction to enhance consumers’ confidence in and valuation of the product.